Comparison of Water Quality between Lattakia and Tartous Drinking Water Intakes of In Al-Sin Lake (Journal of Hama University, 2025)
Tartous and Lattakia governorates are supplied with water from two different locations in Al-Sin Lake. The first governorate draws its water from the feeding springs area of ​​the lake, while the second draws its water away from the springs area. In this research, the water quality of Lattakia and Tartous intakes was compared to determine whether there is significantly spatial difference between them and the need for each of them to be treated before pumping. This was conducted through studying the temporal and spatial changes of several physicochemical and microbial parameters of water quality measured three times monthly in 2021 from both intakes.The research results showed a significant spatial difference between the intakes in the water turbidity, fecal coliform counts, and in dissolved oxygen, ammonia, nitrite and nitrate concentration, in which the parameters values were better in Tartus drinking water intake than Lattakia drinking water intake. The results confirm the necessity for water drawn from Lattakia drinking water intake to be treated before sterilizing and pumping it, while the water drawn from Tartous drinking water intake does not need treatment. The results support the need to modify the current location of Lattakia drinking water purification plant intake, to be in feeding springs area because the plant is not qualified to remove the organic pollutants in this location, especially since they are move in the filtered water to the chemical disinfection stage with chlorine.
Keywords: Al-Sin Lake; Lattakia drinking water intake; Tartus drinking water intake; water quality parameters; temporal changes; spatial changes